University spaces: Creating cité and place (UCL Press, 2019)
This article examines a number of conceptualizations of interactions between people and physical space, and relates them to university settings to make a link with findings on institutional effectiveness. It argues that the idea of the common-pool resource, where certain physical or social conditions are exploited collectively, is a helpful way of understanding how certain university spaces may be used productively. The opposite situation, the creation of a university 'non-place', must be guarded against. Planners and institutional managements can support the creation of high-performing spaces managed in common, while allowing students and others to build their own community structures.